LEVERAGING ARTIFICIAL INTELLIGENCE IN TEACHING AND LEARNING: A REVIEW OF CHALLENGES, OPPORTUNITIES, AND FUTURE DIRECTIONS - Dhingra, Arti; Barkha Rani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Artificial Intelligence (AI) has rapidly emerged as a transformative force in education, particularly during and after the COVID-19 pandemic. This paper reviews existing research on the integration of AI in teaching and learning, examining its role in personalized learning, automated assessments, and enhancing student engagement. The review identifies key challenges such as accessibility issues, data privacy, and teacher readiness. Suggestions for overcoming these challenges include fostering equitable access, ensuring ethical AI implementation, and enhancing teacher training programs. The paper concludes that AI, if strategically implemented, can revolutionize education by fostering inclusivity, efficiency, and innovation.